Kurdish urban politics in the neoliberal era: cases of Diyarbakir and Van mobilized under BDP - Sümer, Bilgesu (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This thesis explores why urban politics became integral for Kurdish movement and how Kurdish movement mobilizes municipalities by examining the cases of Diyarbakir and Van whose municipalities are run by the political party of Kurdish movement, BDP. This study contextualizes the ongoing conflict with neoliberal transformations at the local government level in Turkey. Furthermore, it analyzes the extent to which the motivating factors and reasons for local politics are realized while mobilizing municipalities; given the structural constraints of the conflict and neoliberalism. To address this question, the life trajectories, experience and mobilization of the local actors and activists within their urban localities and local institutions are investigated through ethnography and in depth interviews. This research is an ethnographic fieldwork on an urban social movement with popular composition struggling to steer the wheel of urbanization which occurred ever so rapidly since the 1990s. It is based on my personal engagement and immersion into local activists spheres at the urban localities. It studies two urban localities: Diyarbakir and Van. The argument of the thesis is that local politics became central to Kurdish actors because the experience in mobilizing municipalities have given them the opportunity to address grievances – mostly developed due to the conflict. Meanwhile the project of Democratic Autonomy has given them a field in which how they want to mobilize local governments could be articulated and would be constituted. In this sense, Kurdish movement as a popular urban movement is situated against ill-effects of neoliberalism and is mindful of the conflict and would like to determine the collective consumption at the local and regional level through participatory mechanism to counter problems induced by both contexts.
Keywords: Urbanization -- Turkey -- Diyarbakır İli.; Urbanization -- Turkey -- Van ili.; City planning -- Turkey -- Diyarbakır İli.; City planning -- Turkey -- Van İli; Local government -- Turkey -- Diyarbakır İli.; Local government -- Turkey -- Van İli.